2003
DOI: 10.1086/367917
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Change in Toque Ville: Nouvelle Cuisine as an Identity Movement in French Gastronomy

Abstract: International audienceA challenge facing cultural-frame institutionalism is to explain how existing institutional logics and role identities are replaced by new logics and role identities. This article depicts identity movements that strive to expand individual autonomy as motors of institutional change. It proposes that the sociopolitical legitimacy of activists, extent of theorization of new roles, prior defections by peers to the new logic, and gains to prior defectors act as identity-discrepant cues that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
1,038
2
34

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,218 publications
(1,120 citation statements)
references
References 50 publications
24
1,038
2
34
Order By: Relevance
“…Organizations are also more likely to embrace new policies if they are nonprofit organizations or public agencies that are highly visible because of their large size or if they are more receptive to innovations in employment practices because they have separate personnel offices (Baron, Dobbin, and Jennings 1986;Dobbin et al 1988;Edelman 1990Edelman , 1992. When institutional pressures run counter to the interests of top managers, they may engage in merely symbolic versus real change according to their power vis-à -vis external audiences (Westphal and Zajac 1994) and according to whether the change that is called for is consistent with their backgrounds (Fligstein 1985), their professional identities (Binder 2002;Rao, Monin, and Durand 2003), or the behavior of high-status actors in their organizational field (Rao, Monin, and Durand 2005).…”
Section: Institutional Change In Response To Regulation In the Literamentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations are also more likely to embrace new policies if they are nonprofit organizations or public agencies that are highly visible because of their large size or if they are more receptive to innovations in employment practices because they have separate personnel offices (Baron, Dobbin, and Jennings 1986;Dobbin et al 1988;Edelman 1990Edelman , 1992. When institutional pressures run counter to the interests of top managers, they may engage in merely symbolic versus real change according to their power vis-à -vis external audiences (Westphal and Zajac 1994) and according to whether the change that is called for is consistent with their backgrounds (Fligstein 1985), their professional identities (Binder 2002;Rao, Monin, and Durand 2003), or the behavior of high-status actors in their organizational field (Rao, Monin, and Durand 2005).…”
Section: Institutional Change In Response To Regulation In the Literamentioning
confidence: 99%
“…Institutional theorists have shown that organizational response to institutional pressure is associated with particular environmental characteristics such as dominant beliefs, norms, and resources (e.g., Edelman 1990; Ruef and Scott 1998;Scott et al 2000), regulatory regimes (Tolbert and Zucker 1983;Baron et al 1986;Katzenstein 1998) and communityspecific requirements (Lounsbury 2007;Marquis, Glynn, and Davis 2007), particular organizational characteristics such as alignment with the public sector (Dobbin et al 1988;Edelman 1992), existence of a personnel office (Baron et al 1986;Edelman 1992), and organizational performance (Westphal and Zajac 1994), and particular top-manager characteristics such as work background (Fligstein 1990) and professional identity (Binder 2002;Rao et al 2003). Since Advent and Bayshore were matched on each of these environmental, organizational, and top-manager characteristics, these characteristics alone may not be sufficient for explaining change in an institutionalized work practice.…”
Section: Relational Spaces and The Importance Of Inclusionmentioning
confidence: 99%
“…Haute cuisine is a highly institutionalized field (Ferguson, 1998) that involves various actors (e.g., chefs, critics, restaurateurs), among whom chefs are the dominant players (Rao, Monin, & Durand, 2003). This gives them the power to make more creative contributions than anyone else.…”
Section: Haute Cuisine Chefsmentioning
confidence: 99%
“…Ganter, 2004 ). The power of such creative freedom can be manifested, for example, in the social movement in that a number of elite chefs revolted against the institution of gastronomy and so created the grounds on which the Nouvelle Cuisine was able to emerge ( Rao et al ., 2003 ). At this time, these elite chefs started to abandon a centuries-old symbolic language (cf.…”
Section: Introduction: Background To the Studymentioning
confidence: 99%